2016
DOI: 10.3847/0004-637x/827/1/3
|View full text |Cite
|
Sign up to set email alerts
|

The X-Ray Through Optical Fluxes and Line Strengths of Tidal Disruption Events

Abstract: We study the emission from tidal disruption events (TDEs) produced as radiation from black hole accretion propagates through an extended, optically thick envelope formed from stellar debris. We analytically describe key physics controlling spectrum formation, and present detailed radiative transfer calculations that model the spectral energy distribution and optical line strengths of TDEs near peak brightness. The steady-state transfer is coupled to a solver for the excitation and ionization states of hydrogen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
264
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 212 publications
(277 citation statements)
references
References 64 publications
13
264
0
Order By: Relevance
“…In some parameter regimes, they reproduced the observed very large He IIλ4686/Hβ without invoking a supersolar metallicity of He, which was proposed originally by Peterson & Ferland(1986). Roth et al (2016) considered a model in which both continuum and emission lines are formed in a spherical, optically-thick envelope, whose optical depth to electron scattering is very large. By considering the effect of radiation transfer, they were able to explain the large He II λ4686/Hα with gas at the solar abundance.…”
Section: General Considerationsmentioning
confidence: 89%
“…In some parameter regimes, they reproduced the observed very large He IIλ4686/Hβ without invoking a supersolar metallicity of He, which was proposed originally by Peterson & Ferland(1986). Roth et al (2016) considered a model in which both continuum and emission lines are formed in a spherical, optically-thick envelope, whose optical depth to electron scattering is very large. By considering the effect of radiation transfer, they were able to explain the large He II λ4686/Hα with gas at the solar abundance.…”
Section: General Considerationsmentioning
confidence: 89%
“…Kochanek (2016b) found that stellar evolution can play a role in producing this spectral diversity. Roth et al (2016) modeled the emission from TDEs through an extended, optically thick envelope formed from stellar debris. They find that due to optical depth effects, hydrogen Balmer line emission is often strongly suppressed relative to helium line emission.…”
Section: Composition Of Debrismentioning
confidence: 99%
“…Hence, for the same physical parameters, the lines are far less optically thick than assumed by the CLOUDY models. Roth et al (2015), however, find that extreme hydrogen to helium line ratios are achievable at Solar metallicity using broad line widths and radiation transfer models better suited to high optical depths than CLOUDY.…”
Section: Introductionmentioning
confidence: 99%